Role of melatonin in the angiogenesis potential; highlights on the cardiovascular disease - Afshin Rahbarghazi; Marefat Siahkouhian; Reza Rahbarghazi; Mahdi Ahmadi; Lotfali Bolboli; Rana Keyhanmanesh; Mahdi Mahdipour; Hadi Rajabi (BMC, 2021)
Abstract Melatonin possesses multi-organ and pleiotropic effects with potency to control angiogenesis at both molecular and cellular levels. To date, many efforts have been made to control and regulate the dynamic of angiogenesis modulators in a different milieu. The term angiogenesis or neovascularization refers to the development of de novo vascular buds from the pre-existing blood vessels. This phenomenon is tightly dependent on the balance between the pro- and anti-angiogenesis factors which alters the functional behavior of vascular cells. The promotion of angiogenesis is thought to be an effective strategy to accelerate the healing process of ischemic changes such as infarcted myocardium. Of note, most of the previous studies have focused on the anti-angiogenesis capacity of melatonin in the tumor niche. To the best of our knowledge, few experiments highlighted the melatonin angiogenesis potential and specific regulatory mechanisms in the cardiovascular system. Here, we aimed to summarize some previous experiments related to the application of melatonin in cardiovascular diseases such as ischemic injury and hypertension by focusing on the regulatory mechanisms.